The image of a Russian emigrant on the example of Alexander Galich’s live and works - Skopek, Sandra (Migracja w języku, literaturze i kulturze, 2020)
Alexander Galich is a representative of “The Third Wave” of the Russian emigration, who, however, is less well-known in Poland than other emigrants of this period, like Joseph Brodsky, Sergei Dovlatov or Eduard Limonov. Moreover, in Poland there are no publications devoted entirely to the works of this bard, which cannot be said about other bards – Vladimir Vysotsky and Bulat Okudzhava among others. That is why scientific researches in this area are so important. The main purpose of this article is to show the effects of the forced migration which influence on the poet’s mental condition, his life, the beliefs and, as a result, on the subjects of his works. It should be also noted that Galich’s living in Norway, Germany or France has resulted in the enrichment of the culture of these countries and has influenced on the knowledge of their inhabitants about the realities of life in the Soviet Union. Galich’s songs, mentioned in this article, are about the forced emigration, the life on emigration, the patriotism, the willingness to stay in the homeland, the hope for coming back to the homeland, the dreams of the homeland. All of this has prompted to think about poets and writers who have had to leave their country because of political reasons in Soviet times, nevertheless, theirs lives, development of creative and works are proofs of what is the patriotism of emigrants and how it is possible to raise awareness about the homeland being abroad. Moreover, it is important to note that living abroad has resulted in the idealization of the homeland as well as living on memories only. These issues have been very often raised in Russian works, and the basic dilemmas arising from them are undoubtedly still relevant today.